A Bibliometric Study of Publications and Citations in the Field of Digital Economy - Judijanto, Loso; Uhai, Sabalius; Pratiwi, Lusiana (Westscience Press, 2024)
The evolution of the digital economy has been characterized by an increasing trend in academic publications from 1996 to 2024, reflecting its growing importance and widespread implications across various sectors. This study analyzes the publication trends using bibliometric data, revealing significant growth in research outputs, particularly in the past decade. The implications of this growth are profound for both the business sector and policymakers, as they adapt to technological advancements and shifting market dynamics. The analysis not only highlights the sectors' responses to these changes but also underscores the need for updated policies to support digital infrastructure, ensure data privacy, and promote digital inclusivity. The study further discusses how this burgeoning research can guide strategic decisions in technology adoption and policy formulation.